Effect of Speed of Processing Training on Older Driver Screening Measures - Eramudugolla, Ranmalee (Front Aging Neurosci, 2017)
Objective: Computerized training for cognitive enhancement is of great public interest, however, there is inconsistent evidence for the transfer of training gains to every day activity. Several large trials have focused on speed of processing (SOP) training with some promising findings for long-term effects on daily activity, but no immediate transfer to other cognitive tests. Here, we examine the transfer of SOP training gains to cognitive measures that are known predictors of driving safety in older adults. Methods: Fifty-three adults aged 65–87 years who were current drivers participated in a two group non-randomized design with repeated measures and a no-contact matched control group. The Intervention group completed an average of 7.9 (SD = 3.0) hours of self-administered online SOP training at home. Control group was matched on age, gender and test-re-test interval. Measures included the Useful Field of View (UFOV) test, a Hazard Perception test, choice reaction time (Cars RT), Trail Making Test B, a Maze test, visual motion threshold, as well as road craft and road knowledge tests. Results: Speed of processing training resulted in significant improvement in processing speed on the UFOV test relative to controls, with an average change of -45.8 ms (SE = 14.5), and effect size of ω(2) = 0.21. Performance on the Maze test also improved, but significant slowing on the Hazard Perception test was observed after SOP training. Training effects on the UFOV task was associated with similar effects on the Cars RT, but not the Hazard Perception and Maze tests, suggesting transfer to some but not all driving related measures. There were no effects of training on any of the other measures examined. Conclusion: Speed of processing training effects on the UFOV task can be achieved with self-administered, online training at home, with some transfer to other cognitive tests. However, differential effects of training may be observed for tasks requiring goal-directed search strategies rather than diffuse attention.